Sistem Pendukung Keputusan Penerimaan Official Atlet Pencak Silat Menerapkan Metode OCRA - Fadila Pratiwi (Bulletin of Multi-Disciplinary Science and Applied Technology, 2022)
Official athletes have an important role for an athlete, because the official athlete has the task of preparing all the needs of an athlete both before and after the match is over. With so many duties and responsibilities of an official, an athlete must have a professional official to ensure that all these duties and responsibilities can be carried out. To get a professional official, in the process of selecting new official admissions, you must select prospective applicants objectively so that you will get official results that match the desired criteria. In the official acceptance of pencak silat athletes, there are several problems, namely because of the large number of potential applicants so that they spend quite a long time in the selection. The next problem is that in the selection there are many frauds such as abuse of authority so that they do not get results that are not in accordance with the desired criteria. Therefore, a decision support system (SPK) with the OCRA method is needed which is expected to be able to overcome the problems that occur in the acceptance of official pencak silat athletes. The OCRA method is one of the methods of a decision support system, where this method makes decisions by ranking from the smallest to the largest value. With this system, it is expected to be able to obtain an optimal decision system in the process of receiving official pencak silat athletes.Official Athlete